Ocorrência de inimigos naturais da mosca branca, Bemisia tabaci (Gennadius, 1889) na cultura da soja - Link, Dionisio; Costa, Ervandil Correa (Revista do Centro de Ciências Rurais, 2008)
Larvas e adultos de Chrysopa sp. (Neuroptera, Chrysopidae), Cycloneda sanguinea (L., 1763), Coleomegilla maculata (De Geer,1775) e Eriopis connexa (Germar, 1824) (Coleoptera, Coccinellidae) foram encontrados como predadores da mosca branca, Bemisia tabaci (Gennadius, 1889) (Homoptera, Aleyrodidae) sobre plantas de soja, em Santa Maria, Rio Grande do Sul, Brasil. Abstract Larvae and adults of Chrysopa sp. (Neuroptera, Chrysopidae), Cycloneda sanguinea (L., 1763), Coleomegilla maculata (DeGeer, 1775) and Eriopis connexa (Germar, 1824) (Coleoptera, Coccinellidae) were found eating the white-fly, Bemisia tabaci (Gennadius, 1889), (Homoptera, Aleyrodidae) on soybean plants, at Santa Maria, RS, Brazil.